Demographic and clinical features and prescribing patterns of psychotropic medications in patients with the melancholic subtype of major depressive disorder in China. - Yu-Tao Xiang (Public Library of Science (PLoS), 2012)
Background Little has been known about the demographic and clinical features of the melancholic subtype of major depressive disorder (MDD) in Chinese patients. This study examined the frequency of melancholia in Chinese MDD patients and explored its demographic and clinical correlates and prescribing patterns of psychotropic drugs. Methods A consecutively collected sample of 1,178 patients with MDD were examined in 13 psychiatric hospitals or psychiatric units of general hospitals in China nationwide. The cross-sectional data of patients' demographic and clinical characteristics and prescriptions of psychotropic drugs were recorded using a standardized protocol and data collection procedure. The diagnosis of the melancholic subtype was established using the Mini International Neuropsychiatric Interview (MINI). Medications ascertained included antidepressants, mood stabilizers, antipsychotics and benzodiazepines. Results Six hundred and twenty nine (53.4%) of the 1,178 patients fulfilled criteria for melancholia. In multiple logistic regression analyses, compared to non-melancholic counterparts, melancholic MDD patients were more likely to be male and receive benzodiazepines, had more frequent suicide ideations and attempts and seasonal depressive episodes, while they were less likely to be employed and receive antidepressants and had less family history of psychiatric disorders and lifetime depressive episodes. Conclusions The demographic and clinical features of melancholic MDD in Chinese patients were not entirely consistent with those found in Western populations. Compared to non-melancholic MDD patients, melancholic patients presented with different demographic and clinical features, which have implications for treatment decisions.